KEMUDAHAN DAN E-SERVICE QUALITY TERHADAP MINAT APLIKASI DANA GEN Z KOTA SEMARANG - Amalla, Silvaska; Rahman, M. Fathur (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the effect of ease of use and e-service quality on interest in using the DANA application among Gen Z in Semarang City. The DANA application was chosen as the object of research because it has the best digital performance, even though it is still in fourth position in the number of national e-wallet users. Methods: The research method used is a quantitative approach with survey techniques, involving 102 respondents from Gen Z. The data were collected through questionnaires and analyzed using regression. Results: . The results showed that both ease of use and e-service quality have a positive and significant effect on interest in using the DANA application. Simultaneously, these two independent variables explain 74.7% of the variation in interest in use. This finding confirms the importance of optimizing ease of use and improving digital service quality in maintaining and attracting the young generation of users. This research also provides a practical contribution in the formulation of e-wallet service strategies based on the needs of the digital generation. Keywords: Ease of Use, E-Service Quality, Usage Intention, DANA Application, Gen Z